(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The goal of this paper is to discuss the impact of a participatory management style in a transition phase, primarily in an effort to examine the impact of a participatory management style on resistance to change and its influence on the effectiveness of change. Design methodology approach-Empirical study is addressed after a revision of prior studies to evaluate the nature and indicators of the links between engagement and organizational improvement. The authors used scales and other methods already reported to quantify the key principles, and gain some insight into the interactions between variables through a correlation study. Findings-Data show that participative leadership should provide the organization’s participants with the requisite information to challenge things that may jeopardize adjustments, thereby seeing involvement as an information broker that sheds light on the reform mechanism by growing opposition to sources of reform. Limitations implications of research-The key drawback being the limited survey, as well as the assumption that a sole respondent gives answers. Practical Consequences ‐ This study can allow clinicians to look at opposition to reform from an optimistic point of view, therefore engagement may be considered a way to demonstrate perceived vulnerabilities and help reform agents to enhance the results of transition. Originality value ‐ The paper follows research that provides a constructive interpretation of opposition to transition. In addition , it offers some clues on what kind of origins of opposition to change are more relevant based on the kind of change itself. To analyze the connection between the essence of an industrial organization’s ownership and the effectiveness of participatory management, to research if there is a substantial gap in the effectiveness of participative management between the production and service industries, to research whether there is a gap between the total number of employees